Ketidakpastian Hukum Perlindungan Lahan Pertanian Pangan Berkelanjutan di Tengah Eskalasi Pengadaan Tanah untuk Proyek Strategis Pembangunan Nasional dalam Perspektif Teori Kepastian Hukum - Asyif Faozi; Sri Wahyu Handayani (Jurnal Kajian dan Penelitian Umum, 2026)
This study examines the legal certainty of Sustainable Food Agricultural Land (LP2B) protection amid increasing land acquisition for National Strategic Projects (PSN) in Indonesia. The decline of paddy fields by 803,393 hectares during 2016–2023 reflects the growing pressure on agricultural land conversion. The study focuses on normative conflicts between Law Number 41 of 2009, which emphasizes restrictive protection of LP2B, and the Job Creation Law along with Government Regulation Number 42 of 2021, which promote investment and development facilitation. Using a normative juridical method supported by the theories of Radbruch, Lord Lloyd, Fuller, and Otto, the study finds that the broader definition of public interest under Article 123 of the Job Creation Law creates a multidimensional legal certainty deficit. This includes weakened regulatory stability, reduced predictability, diminished protection of farmers’ rights, and inconsistencies among regulations. The study recommends comprehensive legislative harmonization and stronger integration of LP2B protection into the National Spatial Plan to ensure sustainable agricultural land protection.